COGNITIVE AND BEHAVIOURAL INTERVENTIONS IN DENTAL PATHOLOGY - Vasile Valeriu Lupu; Ciubara Ana Maria; Ancuta Ignat; Aurica Rugina; Violeta Streanga; Adriana Mocanu; Iuliana Magdalena Starcea; Gabriela Paduraru (Romanian Society of Oral Rehabilitation, 2018)
The International Association for the Study of Pain (IASP) defines pain as an unpleasant sensory and emotional experience associated with an actual or potential tissue injury that is described as such, emphasizing the subjective nature. The cognitive-behavioural therapy has begun to be applied for psychosomatic problems in dental problems. There are several types of techniques: relaxation, biofeedback, exposure and cognitive restructuring. In general, therapists may combine several of the above techniques to treat patients with dental anxiety.